Application of disitamab vedotin in the multiline treatment of EGFR mutation-positive lung adenocarcinoma with Her-2 overexpression - Lan, Meiling; Wang, Tianyun; Luo, Diexiao; Chen, Yan; Liang, Wei; Kong, Rui; Xie, Qichao (Frontiers in Oncology, 2024)
ObjectiveTo explore the efficacy of c in the multiline treatment of late-stage lung adenocarcinoma with Her-2 overexpression and epidermal growth factor receptor (EGFR) mutations.MethodsWe summarize the diagnosis and treatment of a female patient with EGFR 21L858R mutation combined with Her-2 overexpression in advanced lung adenocarcinoma, and analyze the effect of c in her treatment process.ResultsThe patient was diagnosed with lung adenocarcinoma 8 years ago. After first-line treatment, the lung lesions enlarged. Following second-line treatment 5 years ago, intracranial metastasis occurred. After third-line treatment 3 years ago, intracranial and lung lesions enlarged. New lesions in the lungs, liver, and spleen appeared after fourth-line treatment 32 months ago. Lung progression occurred after fifth-line treatment 29 months ago. Liver and lung progression occurred after sixth-line treatment 22 months ago. Lung progression occurred after seventh-line treatment 19 months ago. The patient underwent eighth-line treatment with disitamab vedotin (RC48) + lung radiotherapy + liver intervention 13 months ago. Currently, the patient’s condition is stable, with a good quality of life, and the efficacy assessment is stable disease (SD). Conclusion: Her-2 overexpression can occur in late-stage EGFR-mutant lung adenocarcinoma after multiline treatment. RC48 can achieve sustained remission in these patients.